The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jor.24391
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Linear Microcracks and Diffuse Microdamage Following Daily Bouts of Fatigue Loading of Rat Ulnae

Abstract: Microdamage accumulation contributes to impaired skeletal mechanical integrity. The bone can remove microdamage by initiating targeted bone remodeling. However, the spatiotemporal characteristics of microdamage initiation and propagation and their relationship with bone remodeling in response to fatigue loading, especially for more physiologically relevant daily bouts of compressive loading, remain poorly understood. The right forelimbs of 24 rats were cyclically loaded with a ramp waveform for 1,500 cycles/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…The fatigue may give rise to the microdamage in the skeleton mineralized matrix, and ensuing larger bone lesions, ultimately leading to obvious fracture 4,64 . Data analysis has shown that strains of 8000 microstrains enhanced a remarkably increased osteocyte apoptosis in ulnae of rodents 65 . Similarly, it has been indicated that osteocytes will undergo apoptosis once the fatigue induces bone structural microdamage upon overloading 4,64 .…”
Section: Microdamage and Plasma Membrane Disruptionmentioning
confidence: 99%
“…The fatigue may give rise to the microdamage in the skeleton mineralized matrix, and ensuing larger bone lesions, ultimately leading to obvious fracture 4,64 . Data analysis has shown that strains of 8000 microstrains enhanced a remarkably increased osteocyte apoptosis in ulnae of rodents 65 . Similarly, it has been indicated that osteocytes will undergo apoptosis once the fatigue induces bone structural microdamage upon overloading 4,64 .…”
Section: Microdamage and Plasma Membrane Disruptionmentioning
confidence: 99%
“…Herein, we employed a daily ulnar uniaxial compression session model developed by our group, 27 , 28 which mimics the fatigue damage accumulation in soldiers and athletes during physical training. Another single compression session model was also used to compare the “self-repair” rate of post-fatigue damage in various interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, efficient approaches to early protection against bone stress injuries were explored by applying intervention before fatigue loading based on a rat ulnar axial compression model. 22 , 27 , 28 First, we investigated the effectiveness of anabolic PTH and anti-catabolic alendronate (ALN) (two common anti-osteoporotic agents), 29 as well as low-frequency electromagnetic fields (EMFs) and whole-body vibration (WBV), two biophysical modalities with reported osteogenic potential, 30 , 31 on the early prevention of bone stress injuries, and we also optimized the dosage and administration times. We further compared the effects of individual and combinational pharmaceutical/biophysical stimulation on early protection against microdamage accumulation to determine the optimal strategy.…”
Section: Introductionmentioning
confidence: 99%
“…To establish the hind-limb unloading (HU) model, mice were maintained in an approximately 30° head-down-tilt position by tail suspension using a custom-designed Plexiglas cage for 4 weeks. Then, the right tibiae of mice were subjected to daily uniaxial cyclic compressive loading for 2 weeks (5 d/wk) using a custom-designed mechanical loading system as described previously ( 29 , 51 ). The contralateral left tibiae were not loaded and were used as controls.…”
Section: Methodsmentioning
confidence: 99%